Assessing the Association Between Pakistani Women’s Religious Beliefs and Sports Participation - Laar, Rizwan Ahmed; Ashraf, Muhammad Azeem; Zhou, Shu; Zhang, Lei; Zhong, Zhengliang (Frontiers in Psychology, 2022)
Women’s participation in physical activities has been discouraged for a variety of reasons, especially in Muslim countries. This study aims to highlight Pakistani women’s religious beliefs about sports. It focuses on whether their religion contradicts their participation in sporting activities, and it does so by using an adapted version of the Santa Clara Strength of Religious Faith Questionnaire (SCSRFQ) in the theoretical context of feminism in sports. The snowball sampling method was used to select women (n = 357) from the Sindh province of Pakistan, who completed a questionnaire incorporating the SCSRFQ that was specially designed for the current study. The results were unexpected, revealing that religious beliefs have no negative impact on Pakistani women’s participation in sports. Few participants (14 out of 357, 3.9%) believe that religion is an obstacle to their participation in sports. The results of the study challenge the traditional view by most of the previous studies that Islam is against women’s sports. It also challenges cultural limitations, such as some unwritten rules in Pakistani culture according to which women cannot participate in sports. These efforts should lead to enhanced female sports participation in the Pakistani context.